2000
DOI: 10.1590/s0037-86822000000300002
|View full text |Cite
|
Sign up to set email alerts
|

Excito-repellency effect of deltamethrin on triatomines under laboratory conditions

Abstract: This work demonstrates that deltamethrin in low doses produces an excito-repellency effect on triatomines, as already observed for mosquitoes. A wooden box covered with a cloth impregnated with deltamethrin at doses of 2.5 and 5mg ai/m 2 was utilized for the experiment. The triatomine species studied were Triatoma infestans, Panstrongylus megistus, Rhodnius neglectus and Triatoma sordida. Adults were released in one of the sides of the box and their position was noted in subsequent periods. The observations we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…5,24,26,50 Differences in dispersal rates may represent an additional dimension that could interfere in the house infestation capacity of these species. Although T. infestans and P. megistus are known to promptly initiate flight, 51,52 further studies would be necessary to analyze whether differences in flight capacity between them could be related to distinct dispersal rates and spatial distribution. It has also been found that P. megistus is more sensible to temperature shocks than T. infestans, and shows stronger effects after abrupt variations of temperature on ecdysis and survival 53,54 and that P. megistus is much more susceptible than T. infestans to deltamethrin, a piretroid insecticide.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…5,24,26,50 Differences in dispersal rates may represent an additional dimension that could interfere in the house infestation capacity of these species. Although T. infestans and P. megistus are known to promptly initiate flight, 51,52 further studies would be necessary to analyze whether differences in flight capacity between them could be related to distinct dispersal rates and spatial distribution. It has also been found that P. megistus is more sensible to temperature shocks than T. infestans, and shows stronger effects after abrupt variations of temperature on ecdysis and survival 53,54 and that P. megistus is much more susceptible than T. infestans to deltamethrin, a piretroid insecticide.…”
mentioning
confidence: 99%
“…It has also been found that P. megistus is more sensible to temperature shocks than T. infestans, and shows stronger effects after abrupt variations of temperature on ecdysis and survival 53,54 and that P. megistus is much more susceptible than T. infestans to deltamethrin, a piretroid insecticide. 51 Deltamethrin, even at sub-lethal doses, may inhibit re-colonization of households by P. megistus from sylvatic ecotopes. 51 Our results, and those of other reports, 5,24,37,51 reinforce the notion that T. infestans is better pre-adapted for exploiting domiciliary ecotopes than P. megistus.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nymphs fed on treated chickens took 15.1 ± 14.4 mg of blood on each occasion, whereas nymphs fed on control T. infestans response to pour-on cypermethrin • Ivana Amelotti et al 484 chickens took 36.2 ± 24.2 mg. This effect might be due to a repellence response, as seen in Triatoma sordida up to 120 days after the application of 2.5 mg/m 2 of deltamethrin (Diotaiuti et al 2000). Similarly, Alzogaray et al (2000) showed that a repellent component inhibits the feeding of T. infestans third-instar nymphs.…”
mentioning
confidence: 95%
“…Given the specifi city of Triatomine occurrence in household annexes, but the absence of colonization, alternative means of vector control have been tested, including repellents (20) , lining, and/or impregnated curtains (21) (22) (23) . However, the effectiveness of these alternatives requires rigorous assessment.…”
Section: Introductionmentioning
confidence: 99%